2015
DOI: 10.1111/mmi.13076
|View full text |Cite
|
Sign up to set email alerts
|

Swa2, the yeast homolog of mammalian auxilin, is specifically required for the propagation of the prion variant [URE3‐1]

Abstract: SummaryYeast prions require a core set of chaperone proteins including Sis1, Hsp70 and Hsp104 to generate new amyloid templates for stable propagation, yet emerging studies indicate that propagation of some prions requires additional chaperone activities, demonstrating chaperone specificity beyond the common amyloid requirements. To comprehensively assess such prion‐specific requirements for the propagation of the [URE 3] prion variant [URE 3‐1], we screened 12 yeast cytosolic J‐proteins, and here we report a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 99 publications
(175 reference statements)
2
57
0
Order By: Relevance
“…Hsp40, a family of chaperones (~23 in yeast and ~ 43 in Drosophila ) stimulate the ATPase activity of Hsp70 and deliver specific client proteins to Hsp70 [47]. Recent studies found different yeast prions utilizes specific Hsp40 family members [48, 49], suggesting JJJ2 may target a limited number of proteins and may modify Orb2 aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Hsp40, a family of chaperones (~23 in yeast and ~ 43 in Drosophila ) stimulate the ATPase activity of Hsp70 and deliver specific client proteins to Hsp70 [47]. Recent studies found different yeast prions utilizes specific Hsp40 family members [48, 49], suggesting JJJ2 may target a limited number of proteins and may modify Orb2 aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the specific portions of Sis1 required for the propagation of these prions differ, indicating that the exact roles and requirements of chaperone proteins are not universal in yeast prion propagation 6 , 26-30 . In further support of this idea, one of us (JKH) previously determined that an additional J-protein, Ydj1, is required for the propagation of [ SWI + ] specifically, 17 and we recently reported the finding that [ URE3 ] specifically requires the action of a third J-protein, Swa2 1 . Swa2 is the homolog of the mammalian protein auxilin, which is responsible for uncoating clathrin-coated vesicles during clathrin-mediated endocytosis 31 , 32 .…”
mentioning
confidence: 97%
“…Others have also recently reported additional co-chaperone requirements for the propagation of [ URE3 ] 20 . Here we will review our most recent findings regarding Swa2 and prion propagation, 1 present additional data, and discuss these new results in the context of a recently published complementary investigation from another laboratory 20 . Collectively, these investigations suggest that Hsp90 may be the critical binding partner of Swa2 in [ URE3 ] propagation, and we propose a new model for plausible Swa2-Hsp90 cooperation in [ URE3 ] prion propagation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Hsp70s, the cytoplasmic Ssas of Saccharomyces cerevisiae, are necessary for stable prion propagation (33)(34)(35)(36)(37), and can antagonize the curing of [PSI + ] by overproduction of Hsp104 (38), an effect requiring Sgt2 (39). The Hsp40 role in prion propagation includes considerable prion-specificity of the various Hsp40s (40,41). The need for collaboration between Hsp104, Hsp70s, Hsp40s, and nucleotide-exchange factors in prion propagation was shown by the ability of Escherichia coli homologs, ClpB, DnaK, and GrpE, to substitute for their yeast relatives only if they could interact with their E. coli partners (42).…”
mentioning
confidence: 99%